The Importance of Following ACC/AHA Cholesterol Guidelines 2013 by Residents’ Physicians to Reduce Atherosclerotic Cardiovascular Disease in Different Populations Gheith Yousif, MD/MBChB, Kevin Phelps, DO., Robert Gotfried, DO. University of Toledo/Family Medicine Department - Yousif, Gheith; Phelps, Kevin; Gotfried, Robert (Translation: The University of Toledo Journal of Medical Sciences, 2018)
BACKGROUND: The 2013 American College of Cardiology (ACC)/American Heart Association (AHA) cholesterol protocols recommend the use of Pooled Cohort Equations to estimate 10-year and life time Atherosclerotic cardio-vascular disease (ASCVD) risk as a guide for primary prevention treatment options. Many providers underutilize this important tool. OBJECTIVES: To observe resident physicians’ HMG COA inhibitor (statins) prescribing pattern, with particular attention to appropriate dosing as per 2013 ACC/AHA Cholesterol Guidelines, at the University of Toledo Family Medicine Residency Program and to increase Resident Physicians’ awareness of the ASCVD risk calculator as a tool to improve appropriate statin dosing. METHODS: A retrospective, observational, cross-sectioned chart review was performed to analyze pre-existing data collected from a patient population within a defined time period. The study included 237 patient charts, who received care from among 12 Family Medicine Residents. RESULTS: The success rate for correct statins prescriptions for first year residents was 63%, including 24 correct dose prescriptions out of 38 patients total. Second year residents’ success rate increased to 73%, representing 58 correct dose prescriptions out of 80 patients total. Third year residents success rate was 63% with 75 correct dose prescriptions out of 119 patients total. CONCLUSION: Out of 237 chart reviewed, 157 patients received appropriately dosed statin prescriptions, representing a success rate of 66%. This suggests that across all levels of resident training, there is room of improvement in the utilization of the 2013 ACC/AHA lipid lowering guidelines.